DNA Paternity Testing in Lebanon: Ambiguity in Laboratory Practices, Unsolved Ethical Issues, and Need for a Legislative Framework - Azoury, Mirna; Ibrahim, José-Noel; Yassine, Hasan; Abou-Mrad, Fadi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
This study assesses the legal and ethical frameworks for genetic testing in Lebanon, with a particular focus on paternity testing. Information collected from 16 laboratories revealed that paternity testing is performed solely in the four laboratories accredited by the Ministry of Public Health, but only half of the tests are made through the court. Interestingly, one laboratory does not require the parents’ consent prior to paternity testing, and individuals are generally not informed about the possibility of misattributed paternity (73.3%) or disease predispositions (53.3%). Moreover, the disclosure of incidental findings is done by only 37.5% of laboratories. Unfortunately, genetic findings are communicated in the absence of a psychologist in 90% of cases. When deemed necessary, results are shared in 12.5% of cases with other health professionals, without the consent of the patient. Our study highlights the need to develop comprehensive guidelines and regulations that cover paternity testing in Lebanon.